A Short Note on the Knossos Statuette Inscription - Len Gleeson (Heritage, 2021)
For the inscription of the Egyptian statuette in the Heraklion Archaeological Museum, the dedicator’s second title has long been open to question. New and detailed physical evidence, based on optical profilometry, is presented here. The results show errors/omissions in the previously accepted reading and open the way to a much more plausible translation.